Regulation of Alzheimer's disease-associated proteins during epileptogenesis. (1st January 2020) - von Rüden, Eva-Lotta; Zellinger, Christina; Gedon, Julia; Walker, Andreas; Bierling, Vera; Deeg, Cornelia A.; Hauck, Stefanie M.; Potschka, Heidrun
Graphical abstract: Highlights: Proteins linked with Alzheimer pathogenesis are dysregulated during epileptogenesis. Proteins affecting mitochondrial function and calcium homeostasis are dysregulated. Prominent regulation of proteins involved in Aβ processing and regulation. Development and manifestation of both diseases share molecular alterations. Abstract: Clinical evidence and pathological studies suggest a bidirectional link between temporal lobe epilepsy and Alzheimer's disease (AD). Data analysis from omic studies offers an excellent opportunity to identify the overlap in molecular alterations between the two pathologies. We have subjected proteomic data sets from a rat model of epileptogenesis to a bioinformatics analysis focused on proteins functionally linked with AD. The data sets have been obtained for hippocampus (HC) and parahippocampal cortex samples collected during the course of epileptogenesis. Our study confirmed a relevant dysregulation of proteins linked with Alzheimer pathogenesis. When comparing the two brain areas, a more prominent regulation was evident in parahippocampal cortex samples as compared to the HC. Dysregulated protein groups comprised those affecting mitochondrial function and calcium homeostasis. Differentially expressed mitochondrial proteins included proteins of the mitochondrial complexes I, III, IV, and V as well as of the accessory subunit of complex I. The analysis also revealed a regulation of the microtubule associated protein Tau in parahippocampal cortex tissue during the latency phase. This was further confirmed by immunohistochemistry. Moreover, we demonstrated a complex epileptogenesis-associated dysregulation of proteins involved in amyloid β processing and its regulation. Among others, the amyloid precursor protein and the α-secretase alpha disintegrin metalloproteinase 17 were included. Our analysis revealed a relevant regulation of key proteins known to be associated with AD pathogenesis. The analysis provides a comprehensive overview of shared molecular alterations characterizing epilepsy development and manifestation as well as AD development and progression.